2019
DOI: 10.1021/acs.est.8b07192
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of Enteric Pathogens in the Domestic Environment from Human and Animal Sources in Rural Bangladesh

Abstract: Fecal indicator organisms are measured to indicate the presence of fecal pollution, yet the association between indicators and pathogens varies by context. The goal of this study was to empirically evaluate the relationships between indicator Escherichia coli , microbial source tracking markers, select enteric pathogen genes, and potential sources of enteric pathogens in 600 rural Bangladeshi households. We measured indicators and pathogen genes in stored drinking water, soil, and on mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 66 publications
2
63
0
Order By: Relevance
“…The finding that regular interaction with animals may put children at a higher risk of exposure to fecal contamination is consistent with several recent studies examining zoonotic disease transmission in LMICs. 11,45,46 Although the risk was elevated, we find that this exposure is not significantly associated with self-reported child diarrhea in the previous seven days (PR = 2.27; 95% CI: 0.91, 5.67), suggesting that many children are asymptomatic carriers of zoonotic enteric pathogens.…”
Section: Discussionmentioning
confidence: 54%
“…The finding that regular interaction with animals may put children at a higher risk of exposure to fecal contamination is consistent with several recent studies examining zoonotic disease transmission in LMICs. 11,45,46 Although the risk was elevated, we find that this exposure is not significantly associated with self-reported child diarrhea in the previous seven days (PR = 2.27; 95% CI: 0.91, 5.67), suggesting that many children are asymptomatic carriers of zoonotic enteric pathogens.…”
Section: Discussionmentioning
confidence: 54%
“…Evidence of soap served as an indicator for hand washing, thus lack of soap suggests reduced hand washing by the household. Handwashing with soap is especially critical in preventing food and water contamination [7] by ruminants [60], can reduce diarrheal disease risk by between 40% and 65% [61,62], and can protect against exposure to enteric zoonoses found in animal waste [63]. Although good hand hygiene is particularly protective at certain critical times [59], self-reported handwashing rates in this study population were only 20% before food preparation, 27% before eating, 20% before feeding children, 42% after cleaning children, and 76% after using the toilet.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study in Bangladesh showed that animal feces contribute to higher loads of E. coli in soil, water, and food (18). Contributions of animals to E. coli in soil households in rural Bangladesh were further supported by evidence of ruminant-and avian-associated microbial source tracking markers (BacR and avian-GFD, respectively) in soils (20), and an adjunct study to the water, sanitation, and hygiene (WASH) Benefits Trial in rural Bangladesh stressed the importance of animal feces containment (domestic animals were found to be the key contributors to enteric pathogens in household environments) to reduce transmission of pathogens (21). Moreover, increased prevalence and transmission of resistant E. coli variants have also been linked to the use of antimicrobials, which are often unregulated in LMICs (22,23).…”
mentioning
confidence: 89%